👤

Salut pouvez vous m'aider
Réduire les expression suivante :

A = 5 ( a + 2 ) - ( 6a- 7 )
B = b ( 3b + 7 ) + ( 5 - b ) × b
C = -c ( 4 + 3c ) - ( 9 - 2c + 6c ) le 6c est au carré
D = -5d + 5d ( d - 2 ) - 6 ( 7 - 3d )

Merci beaucoup


Répondre :

Bonjour,


Réduire les expressions suivantes :

A = 5 ( a + 2 ) - ( 6a- 7 )

A = 5a + 10 - 6a + 7

A = 5a - 6a + 10 + 7

A = - a + 17


B = b ( 3b + 7 ) + ( 5 - b ) × b

B = 3b² + 7b + 5b - b²

B = 3b² - b² + 7b + 5b

B = 2b² + 12b


C = -c ( 4 + 3c ) - ( 9 - 2c + 6c² )

C = - 4c - 3c² - 9 + 2c - 6c²

C = - 3c² - 6c² - 4c + 2c - 9

C = - 9c² - 2c - 9


D = -5d + 5d ( d - 2 ) - 6 ( 7 - 3d )

D = - 5d + 5d² - 10d - 42 + 18d

D = 5d² - 5d - 10d + 18d - 42

D = 5d² + 3d - 42.

Bonjour,

Réduire les expression suivante :

A = 5 ( a + 2 ) - ( 6a- 7 )

A= 5a+10-6a+7

A= -a+17

B = b ( 3b + 7 ) + ( 5 - b ) × b

B= 3b²+7b+5b-b²

B= 2b²+12b

C = -c ( 4 + 3c ) - ( 9 - 2c + 6c² )

C= -4c-3c²-9+2c-6c²

C= -9c²-2c-9

D = -5d + 5d ( d - 2 ) - 6 ( 7 - 3d )

D= -5d+5d²-10d-42+18d

D= 5d²+3d-42